2022
DOI: 10.3390/land11050599
|View full text |Cite
|
Sign up to set email alerts
|

Do Agricultural Advisory Services in Europe Have the Capacity to Support the Transition to Healthy Soils?

Abstract: The need to provide appropriate information, technical advice and facilitation to support farmers in transitioning towards healthy soils is increasingly clear, and the role of the Agricultural Advisory Services (AAS) in this is critical. However, the transformation of AAS (plurality, commercialisation, fragmentation, decentralisation) brings new challenges for delivering advice to support soil health management. This paper asks: To what extent do agricultural advisory services have the capacity to support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…In line with others, we contend that it is unlikely that increasing knowledge production and knowledge transfer alone will be sufficient to ensure a transition to sustainable soil management (Dalkir, 2005; Ingram et al, 2022; Ingram & Mills, 2019; Rust et al, 2020; Thorsøe et al, 2019). It also needs to be recognised that knowledge is embedded in a wider socio‐material context that enables or constrains the implementation of sustainable soil management, for example, size and type of farm machinery or mode of regulation (Huber‐Stearns et al, 2017; Thorsøe et al, 2022; Visser et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In line with others, we contend that it is unlikely that increasing knowledge production and knowledge transfer alone will be sufficient to ensure a transition to sustainable soil management (Dalkir, 2005; Ingram et al, 2022; Ingram & Mills, 2019; Rust et al, 2020; Thorsøe et al, 2019). It also needs to be recognised that knowledge is embedded in a wider socio‐material context that enables or constrains the implementation of sustainable soil management, for example, size and type of farm machinery or mode of regulation (Huber‐Stearns et al, 2017; Thorsøe et al, 2022; Visser et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…However, often these findings are neither directly applicable to practitioners nor are the underlying data or models (Hessel et al, 2022; Labarthe & Beck, 2022; Potokar et al, 2021). Regarding knowledge use in farming, further implementation barriers are complex and involve fragmentation of advisory services as well as lacking end users' capacities (Ingram et al, 2022; Ingram & Mills, 2019). With respect to SOC, Frelih‐Larsen et al (2017) in a stakeholder consultation found that knowledge gaps are particularly about farm‐level management practices, their effects, economic costs and benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of numerous studies emphasize the importance of improving agriculture in the direction of sustainability [1][2][3][4]. The need for sustainable agricultural solutions that are based on a balance between economic, ecological, and social aspects is becoming more and more pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…The renewed CAP emphasizes the strengthening of knowledge transfer and highlights the importance of the role of the agricultural advisor in the improvement of agriculture [7]. The important role and significant potential for improving the development of sustainable agriculture is beginning to be seen in agricultural advisory services [3,4,[8][9][10]. The advisory service is included as an important segment in the creation of the agricultural innovation system (AIS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation